Strategi Bauran Pemasaran Produk Pos Express (Studi Kasus Kantor Pos Yogyakarta) - , YOSAFAT REMA BAYUAJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study examines the marketing mix strategy Pos Express products available at the Post Office in Yogyakarta. Pos Express product is a product or a document delivery service is fast or flash. Pos Express product is a document delivery service or the fastest, owned by PT Pos Indonesia.This research was conducted to analyze the marketing mix activities that have been carried out by the Post Office in Yogyakarta to the Post Express product, and also to see the response of the users post Express the results of marketing that has been done by PT Pos Indonesia.This research is taking place at the Post Office Yogyakarta.This research seeks to answer the question of how the marketing mix strategy Pos Express products available at the Post Office in Yogyakarta. Results of this study was to Product Pos Express initiated in response to public demand for freight or documents in a flash, while the price charged is the price set by the economic conditions of each placement area.for Post Office Yogyakarta itself based regional strategic aspect which is an area that is heavily populated and economically bustling activity bisnis.for promotional activities carried out by making banners, stickers, billboards, promoting to companies or government agencies. In addition, see the user feedback on the results of the marketing mix that has been conducted, which found that the Post Office Yogyakarta provide good service and low prices in the set Pos Express Service products. The recommendations given in this research is to improve the promotion of creative and service quality on an ongoing basis.